Language Style Of The Main Character In A Little Princess Novel - Putu, Patrisia Sinta Dewi; Komang Sulatra (Institut Agama Islam Negeri Palopo, 2024)
The language style analysis were the main subjects of this study. This study mainly aims to find out the types of language style used by the main character and also analyze the factor influencing language choice in “A Little Princess Novel”. The arrangement of the utterance in the novel is the focus of the language style. Joos (1967) and Holmes (1992) theory was implemented into the data in order to examine the language style and the factor influenced language choice. The data was analyzed using descriptive qualitative method in this study. The data were collected by reading the whole novel, then underlining of each utterances, next classifying the language styles used in each utterances, last step is counting the percentage of the data. According to the findings of the analysis formal style is the high number. The most dominant was formal style 30% percentage that is mostly influenced by the topic factor.